Government Effectiveness dan Kepatuhan: Peran Mediasi Kompleksitas Pajak - Ari Budi Kristanto; Ni Luh Putu Chandrika (Perspektif Akuntansi, 2023)
Tax compliance considered as one of crucial issues in many countries. Aspects of the tax administration system (namely voice and accountability, transparent tax system, and government effectiveness) play an essential role in shaping the taxpayers' behavior. This study aims to examine the role of government effectiveness in improving tax compliance. This study also intends to find out whether tax complexity can mediate this relationship. This study uses secondary data, i.e. government effectiveness scores, tax complexity, and the percentage of tax effort at the country level. The research also uses controlling variables, i.e. democracy index, tax rate, and the rule of law index. The sample of this study consist of 62 countries selected using purposive sampling method. This study found that government effectiveness has no effect on tax complexity. Tax complexity is also proven unable to mediate the effect of government effectiveness on tax compliance.